A study of morphology, UV measurements and zeta potential of Zinc Ferrite and Al2O3 nanofluids. (2022) - Singh, Vinay; Kumar, Ajay; Alam, Mahmood; Kumar, Ashwini; Kumar, Parveen; Goyat, Vikas
Abstract: Nanofluids are generally used as working fluids in heat exchangers and heat transfer equipments because of their unique and improved heat efficacy. But their poor stability due to sedimentation and agglomeration with passage of time has limited them to use in practical applications. Stability of the nanofluids can be increased by addition of surfactants, which induces repulsion between the nanoparticles. Present work focuses on morphology, UV measurements and zeta potential measurements of zinc ferrite and aluminium oxide/water nanofluids. Nanofluids were synthesized by homogeneous mixing of zinc ferrite and aluminium oxide nanoparticles in distilled water to obtain different weight concentrations of the nanofluids using Cetyl Trimethyl Ammonium Bromide as surfactant. Results showed that both the nanofluids offer best dispersion conditions as per zeta potential values, allowing quitehigh stability of the nanofluids. Highest values of absorbance i.e. 3.922 and 3.569 were obtained using 0.5 wt% of the Zinc ferrite and Aluminium Oxide/water nanofluids. Also, highest values of zeta potential i.e. 42.7 and 45.2 mV were obtained using 0.02 wt% of the Zinc ferrite and Aluminium Oxide/water nanofluids.